The Man God Uses - Blackaby, Henry Tom (Nashville Broadman & Holman Publisher, 1999)
Anyone who has ever been called by the voice of God or touched by His hands is eager to know and understand His will for their life. The Man God Uses is a daily study guide encouraging Christian men to examine personal encounters with the Father, and to
Keywords: Christian men -- Religious life